Peintures et sculptures du xixe siècle en Bourgogne, découverte et protection d’un patrimoine méconnu - Michaël Vottero (In Situ)
Like many French regions, Burgundy benefited from an artistic renewal over the course of the 20th century, marked in particular by the commissions of decorations for the churches and the many dispatches of artworks purchased by French State and placed inside the places of worship or the administrations. Since the 1980’s, several of these paintings and sculptures have been classified and protected as ‘Monuments historiques’ and some of them restored. A recent campaign for the location, study and protection of the artworks of the 20th century, launched by the “conservation régionale des Monuments historiques”, the Regional Commission for Historic Monuments and the “conservations départementales des antiquités et objets d’art”, the Local Commissions of Antiquities and Objets d’art of Saône-et-Loire and of Yonne, also helped to promote this theme based on the cathedrals collections, the artists natives of the region, the dispatches from the State and the administrations decorations.